Preparation of Oxidized Starch/β-Lactoglobulin Complex Particles Using Microfluidic Chip for the Stabilization of Astaxanthin Emulsion - Tianxing Wang; Lulu Zhang; Ling Chen; Xiaoxi Li (Foods, 2022)
Here, we designed an oxidized starch/β-lactoglobulin (OS/β-lg) complex colloidal particle using a dual-channel microfluidic chip for the stabilization of astaxanthin emulsion. The effect of the mixing ratio, pH, and the degree of substitution (DS) of the oxidized starch on the formation of OS/β-lg complex particles was investigated in detail. The optimal complexation occurred at a pH of 3.6, a mixing ratio of 2:10, and a DS of 0.72%, giving an ideal colloidal particle with near-neutral wettability. With this optimum agent, the astaxanthin-loaded oil-in-water emulsions were successfully prepared. The obtained emulsions showed the typical non-Newton fluid behavior, and the rheological data met the Herschel–Bulkley model. The microscopic images confirmed the dense adsorption of the particle on the oil/water interface. In vitro release and stability studies demonstrated this compact layer contributed to the controlled-release and excellent stability of astaxanthin emulsions facing heat, ultraviolet, and oxidative intervention. This work suggests the potential of microfluidics for the production of food-grade solid emulsifiers.